Effect of three different lairage times (0, 18 and 24 hours) on meat quality parameters in camels - Hamad, Brahim; Hadef, Leyla; Bellabidi, Meriem; Aggad, Hebib (Acta Biologica Szegediensis, 2024)
Animal stress has frequently been linked to pre-slaughter operations, particularly the transportation and handling process. Therefore, it is assumed that an optimal lairage time before slaughter will exert positive effects on the animal's welfare and meat quality. However, the impact of this practice on camels is unknown. This study aimed to assess the influence of three lairage durations: 0 h (L0), 18 h (L18), and 24 h (L24) on the quality of camel meat. Ninety adult male camels aged 6 years were included in this study. Longissimus lumborum was sampled to analyze for muscle glycogen, muscle pH (45 min; 48 h), muscle temperature (45 min; 48 h), electrical conductivity (45 min; 48 h), drip loss (DL), cooking loss (CL), and thawing loss (TL). The L24 group had the lowest (p < 0.05) of muscle glycogen and the highest ultimate pH (48 h). Further, the L24 group had the lowest muscle temperature, electrical conductivity, drip loss, and thawing loss (p < 0.05). In conclusion, a lairage period of 24 h is recommended in the field conditions studied here for full recovery from stress response caused by the pre-slaughter process and for achieving better camel meat quality.